2016
DOI: 10.5966/sctm.2015-0222
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Preclinical Benchmarks for First-in-Human Trials of Human Embryonic Stem Cell-Based Therapies

Abstract: As research on human embryonic stem cell (hESC)-based therapies is moving from the laboratory to the clinic, there is an urgent need to assess when it can be ethically justified to make the step from preclinical studies to the first protocols involving human subjects. We examined existing regulatory frameworks stating preclinical requirements relevant to the move to first-in-human (FIH) trials and assessed how they may be applied in the context of hESC-based interventions to best protect research participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Preclinical studies have demonstrated that dopamine neurons recovered and motor function improved when hASCs were transplanted into neurotoxin-induced PD models [17,18,25]. Based on these studies, considerations for cell-based clinical trials for PD are currently being discussed [26][27][28][29]. However, most studies only reported a short-term effect following ASC administration, once or twice and intravenously or directly in the SN.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have demonstrated that dopamine neurons recovered and motor function improved when hASCs were transplanted into neurotoxin-induced PD models [17,18,25]. Based on these studies, considerations for cell-based clinical trials for PD are currently being discussed [26][27][28][29]. However, most studies only reported a short-term effect following ASC administration, once or twice and intravenously or directly in the SN.…”
Section: Discussionmentioning
confidence: 99%
“…characteristics that ensure the desired product quality, is difficult for cell products, which are highly complex, change over time, and can be affected by minor changes in the many molecules used in manufacturing. Currently, cell products are defined by a limited number of markers to reflect identity, purity, and potency, but there is recognition that this level of characterization may be inadequate (Barazzetti et al, 2016). We look ahead to improved phenotyping methods, such as single cell-level characterization that better define cell product composition.…”
Section: Challenges In Bringing Ocular Regenerative Therapy To Patientsmentioning
confidence: 99%
“…[2][3][4][5] Well-established benchmarks of acceptable levels of preclinical data in pharmaceutical development enable translation on that landscape to proceed ethically. 6 Even so, Phase 1 clinical trials are the riskiest given the inherent lack of pre-existing data necessary for the ethical justification of research with human subjects. 7,8 Furthermore, phase 1 FIH trials are designed to test for safety and tolerability, not efficacy.…”
Section: Introductionmentioning
confidence: 99%